PENGARUH KUALITAS PELAYANAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) TERHADAP KEPUASAN WAJIB PAJAK PADA KANTOR BADAN PENGELOLAAN PENDAPATAN DAERAH (BAPPENDA) KABUPATEN BOGOR - Hari Subagyo, Wawan; Melliza, Rina (Economicus, 2019)
The tax on Land and Building Rights (BPHTB) is one of the sources of regional acceptance of Bogor District. This research aims to determine the influence of quality of service including simplicity, clarity, certainty, accuracy, security, responsibility, completeness of facilities and infrastructure, ease of access, discipline, politeness and friendliness, and Comfort to the taxpayer satisfaction at the office of BAPPENDA Bogor District. Samples used were 121 respondents. Data analysis techniques using multiple linear regression methods. The results of the analysis show Simplicity (X1), Certainty time (X3), Responsibility (X6) and Ease of Access (X8) does not affect the taxpayer satisfaction (Y). While the Variable Clarity (X2), Accuracy (X4), Security (X5), Completeness of Facilities and Infrastructure (X7), Discipline, Courtesy and Friendliness (X9) and Convenience (X10) affect the Satisfaction of Taxpayers (Y) at BAPPENDA Office of Bogor District.